Green Talk: Comparing the Discourse on Climate Change and Sustainable Development between Environmental NGOs and the State in Vietnam and Bolivia - Schipani, Samantha (Consilience, 2015)
Environmental non-government organizations (ENGOs) and national governments are key players in the political sphere surrounding issues of climate change and sustainable development. The relationships between the discourse on “climate change” and “sustainable development” and ENGOs and the state in both Vietnam and Bolivia provides a critical look into the ways in which these issues are approached in two highly-vulnerable countries with different political regimes. Live & Learn, the Centre for Marinelife and Conservation, and PanNature were interviewed as ENGO case studies in Vietnam; and Grupo de Trabajo de Cambio Climático y Justicia and Proinpa were interviewed as ENGO case studies in Bolivia. Comparing the discourse from the ENGO interviews and websites depicting the Socialist Republic of Vietnam’s Law on the Protection of the Environment and Bolivia’s 2009 Political Constitution of the State elucidates the gaps left by state policies with regards to the needs of civil society in the context of climate change and sustainable development. The analysis also demonstrates the ways in which different regimes shape the culture of ENGOs and how this impacts climate change and sustainable development initiatives and action.